The phenomenology of the anorexic body - Shapiro, Joel (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The purpose of the study is to articulate the phenomenology of the anorexic body. In order to describe the complex meaning of the anorexic body, the present research adopts the qualitative and exploratory approach of Seidman's (1991) in-depth phenomenologically based interviewing method. This involves a series of three separate interviews, with three research participants who have had personal experience of anorexia. The method of data analysis used is essentially on editing style of analysis (Miller and Crabtree, 1992) and is based on a hybrid of the grounded theory approach of Glaser and Strauss (1967) and Heidegger's (1927) ontological hermeneutics to form what Addison (1992) calls grounded interpretive research. Anorexic embodiment is conceptualised as precipitating a fundamental disturbance between the interactions of embodied consciousness and the world. The body is no longer taken-for-granted, and becomes an object for scrutiny. As an object, the body is experienced as a thing exterior to the self, and this awareness contributes to the sense of qisorder which permeates anorexic embodiment. Bodily intentionality is frustrated when the sphere of bodily actions and habitual acts become circumscribed. The character of lived temporality and lived spatiality are also effected with the anorexic's focus on the now, ushering in a spatiality of the here. These findings indicate that anorexic embodiment is experienced primarily as a disruption of the 'lived body' rather than that of the biological body. The prevailing discourses of anorexic embodiment are shown to be split between the naturalized discourses that provide a model of the body that is biologically determined and ahistorical, and the denaturalized discourses that provide a model of the body that is culturally constructed and lacks embodied givenness. It is argued that Merleau-Ponty's phenomenology of the body offers a renaturalization of the body that overcomes the nature/culture dichotomy of the naturalized and denaturalized discourses, thereby providing a solid foundation that more directly addresses the phenomenology of the anorexic body. The theoretical and treatment implications of Merleau-Ponty's renaturalization of the anorexic body are highlighted, and suggestions for further research are presented.
Keywords: Anorexia nervosa; Eating disorders; Anorexia nervosa -- Psychological aspects